2005
DOI: 10.3354/dao064193
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the major capsid protein gene of iridovirus isolates from cultured flounders Paralichthys olivaceus in Korea

Abstract: In 2003, 13 isolates of iridovirus were obtained from cultured flounders Paralichthys olivaceus during epizootics in Korea. The full open reading frames (ORFs) encoding the major capsid protein (MCP) (1362 bp) from the 13 flounder iridoviruses (FLIVs) were sequenced and the deduced amino acid sequences were phylogenetically analyzed. Phylogenetic analysis of the MCP revealed that all 13 FLIVs were the same species as rock bream iridovirus (RBIV), red sea bream iridovirus (RSIV), and infectious spleen and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…It is likely that the importation of infected seedlings captured in the South China Sea was responsible for the introduction of RSIV into Japan. In addition, epizootics of RSIV-induced disease occurred in farmed red sea bream, rock bream, Japanese flounder ( Paralichthys olivaceus ), and turbot ( Scophthalmus maximus ) in Korea (Jung et al 2000, Do et al 2005a, and in mandarin fish ( Siniperca chuatsi ) reared in offshore pens in the South China Sea (He et al 2000) as well as in stocks of amberjack seedlings from Hainan Island. Although most studies to date have focused solely on identifying the viral agent responsible for disease, and developing accurate diagnostic tools, the transcriptional program of RSIV has recently been elucidated using DNA microarray technology (Lua et al 2005(Lua et al , 2007.…”
Section: Isolation and Characterization Of Rsivmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the importation of infected seedlings captured in the South China Sea was responsible for the introduction of RSIV into Japan. In addition, epizootics of RSIV-induced disease occurred in farmed red sea bream, rock bream, Japanese flounder ( Paralichthys olivaceus ), and turbot ( Scophthalmus maximus ) in Korea (Jung et al 2000, Do et al 2005a, and in mandarin fish ( Siniperca chuatsi ) reared in offshore pens in the South China Sea (He et al 2000) as well as in stocks of amberjack seedlings from Hainan Island. Although most studies to date have focused solely on identifying the viral agent responsible for disease, and developing accurate diagnostic tools, the transcriptional program of RSIV has recently been elucidated using DNA microarray technology (Lua et al 2005(Lua et al , 2007.…”
Section: Isolation and Characterization Of Rsivmentioning
confidence: 99%
“…Recent analyses of the amino acid sequences of the major capsid protein (MCP) and other viral proteins confirmed these taxonomic divisions and indicated that species within a genus generally shared high levels of identity/similarity. Typically, members of the same viral genus show more than 70% similarity within the major capsid protein (MCP) at the amino acid level, whereas species from different genera show less than 50% similarity (Do et al 2005a(Do et al , 2005b.…”
Section: Taxonomymentioning
confidence: 99%
“…The family Iridoviridae is subdivided into five genera, Iridovirus, Chloriridovirus, Ranavirus, Lymphocystisvirus, and Megalocytivirus, as proposed by the eighth report of the International Committee on Taxonomy of Viruses (3). In recent years, megalocytiviruses have received increasing attention due to the ecological and economic impact that these viruses have on wild and cultured fish (1,5,21). Infectious spleen and kidney necrosis virus (ISKNV), the type species of the genus Megalocytivirus, is devastating to the mandarin fish farm industry in China.…”
mentioning
confidence: 99%
“…The phylogenetic tree based on MCP gene nucleotide sequences revealed that 33 megalocytiviruses were divided into three major clusters as described previously [31,33] ( . 1) and the range of nucleotide sequence identities was greater than 96.2% (Table 3); the genotype II included ISKNV-DW, ISKNV-XH, ISKNV-HZhm, ISK-NV-NZh, ISKNV-QY, ALIV, MCIV, DGIV (Fig.…”
Section: Genotype Analysis Of 33 Megalocytivirusesmentioning
confidence: 99%
“…Recently, megalocytiviruses were divided into three genotype based on the MCP gene [30][31][32]. In this article, the complete MCP genes of nine ISKNV isolates from infected mandarin fish and Japanese Amberjack cultured in different area in Guangdong, China, were sequenced and compared with other known megalocytiviruses to evaluate genetic variation and host range of the viruses.…”
Section: Introductionmentioning
confidence: 99%